Health-Related Quality of Life Evaluation Using the Short Form-36 in Patients With Human T-Lymphotropic Virus Type 1-Associated Myelopathy - Kimura, Miyuna; Yamauchi, Junji; Sato, Tomoo; Yagishita, Naoko; Araya, Natsumi; Aratani, Satoko; Tanabe, Kenichiro; Horibe, Erika; Watanabe, Toshiki; Coler-Reilly, Ariella; Nagasaka, Misako; Akasu, Yukari; et al. (Frontiers in Medicine, 2022)
Background: Human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a rare neuroinflammatory disease, causing various neurological symptoms, including motor, sensory, and bladder and bowel dysfunctions. This study was designed to reveal the impact of HAM/TSP and related symptoms on health-related quality of life (HRQoL). Methods: We analyzed the Short Form-36 (SF-36) and clinical data of 538 patients with HAM/TSP registered in the HAM-net, a nationwide patient registry for HAM/TSP in Japan. HRQoL was evaluated using the SF-6D (a health state utility value calculated from the SF-36) and eight SF-36 subscales. A general liner model was used to estimate the impact of major HAM/TSP-related symptoms, including gait dysfunction, sensory disturbance in the legs (pain and numbness), urinary dysfunction, and constipation, on the SF-6D and SF-36 subscale scores. Results: The mean age and disease duration were 62.0 and 16.5 years, respectively. Of the patients, 73.2% needed walking aid; 42.7% and 67.1% had leg pain and numbness, respectively; 92.1% had urinary dysfunction; and 77.9% had constipation. The mean SF-6D score was 0.57, which was substantially lower than the national average (0.66 in females and 0.69 in males in their 60s), exceeding the minimal importance difference (0.05–0.1). All major symptoms were significantly associated with a decrease in the SF-6D score. While all SF-36 subscale scores were below the national standard of 50, physical functioning (PF) was the worst with an average score of 18.9 points. Gait dysfunction was associated with lower scores in PF, limitations on role functioning because of physical health, bodily pain, general health perception (GH), vitality (VT), and social functioning (SF); however, no association was observed between gait dysfunction and limitations on role functioning because of emotional problems and mental health (MH). Meanwhile, sensory disturbance in the legs was associated with a decrease in scores in all subscales. Urinary dysfunction was associated with worse PF, GH, VT, and MH. Constipation was associated only with PF. Conclusion: HRQoL of patients with HAM/TSP was worse than that of the general population and was associated with all major symptoms. Thus, patients should be comprehensively managed to achieve better HRQoL.